THE ROLE OF AI IN AUTONOMOUS VEHICLE DELIVERY WITH PERSONALIZATION AND ALGORITHMS - Rathnakumar Udayakumar (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2023)
Autonomous vehicle delivery is rapidly becoming a popular mode of transportation for goods, thanks to advancements in AI and machine learning. This white paper explores the role of AI and algorithms in autonomous vehicle delivery, specifically focusing on personalization and algorithms. By providing personalized delivery options and real-time updates, personalization improves customer satisfaction and loyalty, while algorithms optimize delivery routes and schedules, enabling efficient and cost-effective delivery. However, there are also challenges and limitations to using these technologies, including privacy concerns, regulatory challenges, and technological limitations. The future of autonomous vehicle delivery is promising, with continued innovation and adoption of these technologies expected in the years to come.